Analisis Asuhan Keperawatan pada Pasien dengan Stroke Iskemik dan Intervensi Range of Motion (ROM) Pasif di Ruangan Edelweis 1 RS. Prof. Dr. R. D. Kandou Manado - Wenas, Missheyla Jhulietha; Toar, Juwita Moreen; Fitriani, Fitriani (Mapalus Nursing Science Journal, 2024)
Background: Chronic kidney disease (CKD) that reaches its final stages often requires hemodialysis therapy to replace lost kidney function. Although hemodialysis is effective in the management of this condition, CKD patients who undergo the procedure often experience musculoskeletal complications, including impaired blood circulation in the lower extremities. This can cause swelling (edema). One non-pharmacological approach that can help improve blood circulation and reduce swelling is physical therapy, especially ankle pump exercises and leg elevation. Objective: To explain nursing care for patients undergoing hemodialysis with the application of Ankle Pump Exercise therapy combined with 300 Leg Elevation in the Melati Hemodialysis Room, Kandou Manado Hospital. Method: Case study with nursing care approach that includes assessment, data analysis, nursing planning, then applied to patients with implementation and evaluation that focuses on providing nursing care with nursing process and additional intervention based on journal of application of ankle pump exercise therapy combination of 300 leg elevation. Results: Assessment of edema on the first day of edema degree IV duration of more than 2 minutes, assessment of edema on the fourth day of edema degree IV duration of 1 minute 45 seconds, and assessment of edema on the eighth day of edema degree III duration of 57 seconds. Conclusion: Provision of nursing care to Mrs. J with the application of ankle pump exercise therapy intervention and 30 degree leg elevation has proven to be beneficial in reducing edema in patients. Keywords: Chronic Kidney Disease (CKD), edema, ankle pump exercise, leg elevation.